Sosialisasi dan Praktik Langsung Terkait Peran Guru sebagai Fasilitator Trauma Healing bagi Anak-anak Sekolah Korban Bencana di Kota Palu - Dwiningtias, Hamidah; Hayatul Khairul Rahmat (PT Hakhara Akademia Indonesia, 2025)
Teachers’ awareness of trauma experienced by children is the main foundation in efforts to create a learning environment that supports post-disaster psychosocial recovery, especially in 3T areas that are vulnerable to various forms of crisis. Teachers who have a high awareness of the impact of trauma will be more sensitive in recognizing signs of emotional and behavioral disorders in students, such as excessive anxiety, withdrawal, difficulty concentrating, or drastic changes in attitude. This awareness is not only limited to theoretical knowledge, but also includes deep empathy and sensitivity to students’ social, cultural, and personal backgrounds. Teachers who are aware of children’s trauma will try to avoid a harsh or coercive approach in the learning process, and instead will prefer flexible, supportive, and positive reinforcement methods. In addition, teachers who understand the importance of trauma recovery will be more proactive in finding solutions, such as coordinating with schools, families, or professionals to provide appropriate interventions. In this context, teacher training and coaching on trauma-informed education is very important so that this awareness can be systematically increased. With this awareness, teachers do not only become educators, but also protectors and companions who help students through difficult times, so that the learning process can be more humane and meaningful.